Takayasu arteritis: a comprehensive review of literature - Bishnoi, Ravin K.; Devi, Shivani; Rai, Shivani; ., Gunjot (International Journal of Research in Medical Sciences, 2020)
Takayasu arteritis is an inflammatory pulseless disease of large arteries with unknown etiology which advances in three stages i.e. early systemic, vascular, and burnout stage. It is more prevalent in Asian women of childbearing age. Hypertension, fever, weight loss, arthralgia, limb claudication, light-headedness, and arterial pain are common manifestations. Angiography is a gold standard test to evaluate TA. There is no reliable serological marker has been identified. Control on the inflammatory process and hypertension are two imperative angles to treat the disease. Steroids are most used. Reconstructive surgeries are limited to severe and stenotic lesions. This review aims to report comprehensive evidence about Takayasu arteritis. We conducted an integrative review of theoretical and empirical publications reporting epidemiology, etiopathogenesis, classification, diagnostic evaluation, and management of TA. The authors searched PubMed, Embase, and Scopus until March 2020. A total of 1104 records found, we included 37 papers for review after reading the articles. Remaining was excluded because of no innovative content, insufficient details, and no clear endpoints. This review of the literature presents comprehensive evidence in all fields of TA. Still, large areas need to be studied for better management of patients with TA.